2015
DOI: 10.1007/s00280-015-2944-z
|View full text |Cite
|
Sign up to set email alerts
|

p53 overexpression increases chemosensitivity in multidrug-resistant osteosarcoma cell lines

Abstract: Purpose Multidrug resistance (MDR) is a major obstacle to the successful treatment of osteosarcoma with chemotherapy. Effectiveness of cancer therapy correlates with the ability to induce a p53-dependent apoptotic response. p53 is a tumor suppressor gene that is mutated in 22% of osteosarcomas. While impaired p53 has been implicated in the oncogenesis of osteosarcoma, it is unclear whether overexpression of wild type p53 can increase chemosensitivity in MDR osteosarcoma cells. Methods We transfected a plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 53 publications
2
28
1
Order By: Relevance
“…CDDP and CFC in combination may induce apoptosis by activating DNA damage. The present study is in agreement with that of Ye et al (40), which found that expression of p53 could lead to the induction of apoptosis by activating DNA damage in osteosarcoma cell lines. One limitation of the present study is that the expression of proteins involved in apoptotic pathways was not determined.…”
Section: Value Dri Value -----------------------------------------supporting
confidence: 94%
“…CDDP and CFC in combination may induce apoptosis by activating DNA damage. The present study is in agreement with that of Ye et al (40), which found that expression of p53 could lead to the induction of apoptosis by activating DNA damage in osteosarcoma cell lines. One limitation of the present study is that the expression of proteins involved in apoptotic pathways was not determined.…”
Section: Value Dri Value -----------------------------------------supporting
confidence: 94%
“…These results indicate that knock‐out mutant TP53 and restoration of the wild‐type TP53 function can increase the chemosensitivity of MDR osteosarcomas. Previously, we have reported that the overexpression of wild‐type TP53, through plasmid transfection, could enhance the effect of doxorubicin in the KHOSR2 cell line . Also, Zhang et al previously reported that mutant TP53 inhibits the activation of p73, leading to chemoresistance in tumors.…”
Section: Discussionmentioning
confidence: 87%
“…Previously, we have reported that the overexpression of wild-type TP53, through plasmid transfection, could enhance the effect of doxorubicin in the KHOSR2 cell line. 48 Also, Zhang et al previously reported that mutant TP53 inhibits the activation of p73, leading to chemoresistance in tumors. NSC59984 was able to restore the activity of p73, and consequently repaired the wild-type TP53 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutant p53 (mutp53) is highly expressed in 40‐50% of all human tumors. Mutp53 generates aberrant proteins with abrogated tumor suppressor functions that can also acquire oncogenic gain‐of‐functions (GOF) that promotes malignant progression, invasion, metastasis and chemoresistance . SGC‐7901 was a cell line with mutated p53 (http://p53.free.fr).…”
Section: Discussionmentioning
confidence: 99%